Time-Resolved Spectroscopic Study on the Photoredox Reaction of 2-(p-Hydroxymethyl)phenylAnthraquinone - Qingqing Song (Nature Portfolio, 2017)
Abstract In this work, we report a combined time-resolved spectroscopic and density functional theory computational study on 2-(p-hydroxymethyl)phenylanthraquinone (PPAQ) in which the benzyl alcohol moiety is significantly farther away from the AQ ketone group compared to the compound 2-(1-hydroxyethyl) 9,10-anthraquinone (HEAQ) so as to investigate the photophysical and photochemical reactions of PPAQ in several solvents, especially for the photoredox reaction in a pH 2 aqueous solution. The results here indicate that PPAQ undergoes the photoredox reaction via a two-step pathway and that the low efficiency of the photoredox reaction of PPAQ compared to the related HEAQ molecule is caused by the longer distance between the benzyl alcohol moiety and the AQ ketone moieties.